Analysis of the Need for Developing Palm Oil Industry–Based Augmented Reality Media to Improve Energy Literacy and Physics Concept Understanding in Vocational Schools - Erazando Alfa Seira; Apit Fathurohman; Hamdi Akhsan (Postgraduate, University of Mataram, 2026)
This study aims to analyze the need for the development of augmented reality (AR)-based learning media in the context of the palm oil industry to improve students' energy literacy and understanding of physics concepts at vocational high schools. The study used a survey method with a descriptive quantitative approach. The research subjects consisted of 62 tenth-grade students at the Sembawa State Agricultural Vocational High School, who were selected using purposive sampling. The research instrument was a five-point Likert scale questionnaire that had been tested for content validity using Aiken's V index and for reliability using Cronbach's Alpha. The results showed that students had a high interest in learning physics, but their understanding of concepts and energy literacy was still in the moderate category. In addition, the learning media used were not yet able to optimally visualize physics processes in the context of the palm oil industry. These findings indicate the need to develop contextual, interactive, and relevant AR-based physics learning media for vocational education. This research provides practical implications in the form of recommendations for the design specifications of palm oil industry–based AR media.